Discovering hidden degradation using ultrasonic wave propagation: theory and experimentation - Mukherjee, Abhijit (tbc, 2013)
Building and maintenance of civil infrastructure is one of the largest contributors in global warming. Extending the life of infrastructure through regular monitoring and retrofitting can reduce environmental damage to a great extent. Inspection, diagnosis and prognosis of damage in installations are imperative for avoiding their catastrophic failures. This paper illustrates the ability ultrasonic guided waves to pick up the signatures of structural damage. Discovering hidden degradations such as corrosion inside reinforced concrete and submerged plated structures has been demonstrated. The theoretical development of propagation of ultrasonic waves is also reported.